Aggressive presentation of multiple myeloma as renal failure and pathological fracture of dorsal vertebra in a young patient: a rare case report - kumar Kalita, Lohit; Kalita, Chayanika; Kumar Gogoi, Pabitra; Ch. Sarma, Umesh (International Journal of Medical Research and Review, 2015)
Multiple myeloma presenting with acute renal failure with dorsal vertebral fracture is extremely rare phenomenon. Renal failure in multiple myeloma is associated with Light chain myeloma, serum creatinine more than 4mg/dL, extensive proteinuria and early infections. Our patient was a 29 -year-old male with multiple poor prognostic factors for renal failure. He presented with sudden onset pain in the backbone with weakness of lower extremities and loss of bowel and bladder control. On neurological examination – power of lower extremities was 4/5 with sign of sensory deficit at below umbilicus. He was diagnosed as lamda type nonsecretory multiple myeloma. He was started with malphalalan-prednisolone regimen but succumb to his disease process after one week.